Best practice in working with children who have developmental language disorder: a focused review of the current research evidence base (article in Czech translation) - Hazel Roddam; Jemma Skeat (Listy klinicke logopedie, 2020)
The purpose of this paper is to provide a synthesis of the current international research evidence base regarding best practice in the diagnosis and treatment of children with language disorders. We begin with a discussion about the terminology used and how this relates to identification and diagnosis, and then describe assessment and treatment practices. The discussion of intervention and case management of these children focuses on the use of high quality evidence that presents an overview of treatment approaches, rather than specific treatment programmes that may not be relevant to all international practice settings. The paper sets the context of the wider international research evidence base: we also include commentary that may be more relevant to some countries across mainland Europe, and specifically to the Czech Republic context. Research studies that reflect local languages and culture are a highly important component of the evidence base for practice, but these should be considered in the context of international consensus evidence. In particular, some strategic recommendations are made to address the inherent challenges of sustaining best practice where open access to evidence sources may be constrained.